2023
DOI: 10.7554/elife.87037
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal discoidin domain receptor signaling strengthens integrin adhesion to connect adjacent tissues

Abstract: Separate tissues connect through adjoining basement membranes to carry out molecular barrier, exchange, and organ support functions. Cell adhesion at these connections must be robust and balanced to withstand independent tissue movement. Yet, how cells achieve synchronized adhesion to connect tissues is unknown. Here, we have investigated this question using the C. elegans utse-seam tissue connection that supports the uterus during egg-laying. Through genetics, quantitative fluorescence, and cell specific mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…The two main receptors for type IV collagen are integrin and the discoidin domain receptor (DDR). DDR2, one of the two DDR genes, plays a role in promoting attachment at the tissue linkage site in utse and seam cells [ 34 ]. Several studies have demonstrated the critical role of DDR2 in breast cancer progression and metastasis, both in tumor cells and stromal cells [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The two main receptors for type IV collagen are integrin and the discoidin domain receptor (DDR). DDR2, one of the two DDR genes, plays a role in promoting attachment at the tissue linkage site in utse and seam cells [ 34 ]. Several studies have demonstrated the critical role of DDR2 in breast cancer progression and metastasis, both in tumor cells and stromal cells [ 35 ].…”
Section: Discussionmentioning
confidence: 99%